2011
DOI: 10.1111/j.1748-1716.2010.02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine activates preferentially α1-isoform of 5′AMP-activated protein kinase in rat skeletal muscle

Abstract: Our results suggest that of the two α isoforms of AMPK, AMPKα1 is predominantly activated by caffeine via an energy-independent mechanism and that the activation of AMPKα1 increases glucose transport and ACC phosphorylation in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 61 publications
6
72
0
3
Order By: Relevance
“…Also, caffeine activates cyclic AMP-dependent protein kinase through an insulin-independent mechanism, which increases AMP kinase-1 to promote glucose transport. Caffeine antagonizes the adenosine A1 receptors in skeletal muscles, which improves glucose tolerance in rats [27]. These mechanisms may partially explain the reported hypoglycemic effect of caffeine in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…Also, caffeine activates cyclic AMP-dependent protein kinase through an insulin-independent mechanism, which increases AMP kinase-1 to promote glucose transport. Caffeine antagonizes the adenosine A1 receptors in skeletal muscles, which improves glucose tolerance in rats [27]. These mechanisms may partially explain the reported hypoglycemic effect of caffeine in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…from the SR (Palade 1987) or affect Ca 2? activation of varied skeletal muscle fibers (Posterino and Dunn 2008), activating the 5 0 AMP-activated protein kinase (AMPK) (Egawa et al 2011;Jensen et al 2007), and reducing plasma K ? levels (Lindinger et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies have indicated that long-term coffee consumption is associated with a reduced risk of developing T2DM [19,20]. Our recent studies [21,22] reported that caffeine, the major constituent of coffee, acutely increases AMPKα Thr 172 phosphorylation, an essential step for kinase activation [23] and insulin-independent glucose transport in rat skeletal muscles. Although our results suggest that caffeine is an active compound responsible for the antidiabetic effect of coffee, coffee is a complex mixture of hundreds of chemicals that occur naturally or are formed during the roasting process.…”
Section: Introductionmentioning
confidence: 97%